2019
DOI: 10.1038/s41598-019-44919-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of azole sensitivity and filamentation by GPI15, encoding a subunit of the first GPI biosynthetic enzyme, in Candida albicans

Abstract: Glycosylphosphatidylinositol (GPI)-anchored proteins are important for virulence of many pathogenic organisms including the human fungal pathogen, Candida albicans . GPI biosynthesis is initiated by a multi-subunit enzyme, GPI- N- acetylglucosaminyltransferase (GPI-GnT). We showed previously that two GPI-GnT subunits, encoded by CaGPI2 and CaGPI19 , are mutually repressive. CaGPI19 also co-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…A third subunit has been described, GPI15, a master activator of GPI2 and GPI19, important for growth, cell wall integrity, and GPI synthesis in C. albicans. GPI15 mutants were hypofilamentous, ergosterol defective, and azole sensitive and exhibited the phenotypes of both GPI2 and GPI19 mutants [96]. Additionally, GPI15 mutants were less virulent in vitro, since this gene regulates hyphal filamentation and invasive growth, which are important for the establishment of the infection by C. albicans (Table 1) [96].…”
Section: Relevance Of Glycosylphosphatidylinositol Anchors During Host-pathogen Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third subunit has been described, GPI15, a master activator of GPI2 and GPI19, important for growth, cell wall integrity, and GPI synthesis in C. albicans. GPI15 mutants were hypofilamentous, ergosterol defective, and azole sensitive and exhibited the phenotypes of both GPI2 and GPI19 mutants [96]. Additionally, GPI15 mutants were less virulent in vitro, since this gene regulates hyphal filamentation and invasive growth, which are important for the establishment of the infection by C. albicans (Table 1) [96].…”
Section: Relevance Of Glycosylphosphatidylinositol Anchors During Host-pathogen Interactionmentioning
confidence: 99%
“…GPI15 mutants were hypofilamentous, ergosterol defective, and azole sensitive and exhibited the phenotypes of both GPI2 and GPI19 mutants [96]. Additionally, GPI15 mutants were less virulent in vitro, since this gene regulates hyphal filamentation and invasive growth, which are important for the establishment of the infection by C. albicans (Table 1) [96]. Thus, by controlling Gpi12 and Gpi19 activities, Gpi15 may be a good antifungal target.…”
Section: Relevance Of Glycosylphosphatidylinositol Anchors During Host-pathogen Interactionmentioning
confidence: 99%
“…In a genome-wide screen CSF1 was implicated in maturation of glycosylphosphatidylinositol (GPI), a posttranslational modification that allows proteins to be targeted to the cell membrane (Čopič et al 2009). Genes involved in this maturation process have been shown to regulate ERG11 in Candida albicans and can thus modulate azole resistance (Jain et al 2019). Genome-wide genetic interaction mapping experiments have shown that the interaction profile of CSF1 is similar to that of many genes involved in cell surface GPI anchor maturation (Table S14) (Usaj et al 2017).…”
Section: Connection Between Csf1 and Azole Resistancementioning
confidence: 99%
“…Recently, we have shown that Rtt109 mediated acetylation of H3 regulates the expression of genes involved in GPI anchor biosynthesis and in ergosterol biosynthesis (18). However, the crosstalk between Rtt109 and Fun30 has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rtt109 in C. albicans has been linked to pathogenesis; the cells lacking Rtt109 were found to be sensitive to genotoxic agents like camptothecin (CPT) and methyl methane sulfonate (MMS) indicating the role of the histone acetyltransferase in DNA damage response/repair (14). Recently, we have shown that Rtt109 mediated acetylation of H3 regulates the expression of genes involved in GPI anchor biosynthesis and in ergosterol biosynthesis (18). However, the crosstalk between Rtt109 and Fun30 has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%